Case report: Acute pancreatitis in lung adenocarcinoma with small cell transformation after multiple line targeted therapy - Jing, Yaoyao; Li, Xiaoxiao; Sun, Xiaoyuan; Ren, Minghan; Xiao, Ruoxi; Zhao, Jiayu; Liu, Zimin (Frontiers in Oncology, 2024)
In lung cancer, metastasis to the liver, bones, brain, and adrenal glands is more commonly observed, whereas pancreatic metastasis from lung cancer is relatively rare. We present a case of a patient with an 8-year history of lung adenocarcinoma (LUAD) who was admitted to our institution exhibiting symptoms consistent with acute pancreatitis. Subsequent histopathological examination through puncture confirmed the occurrence of pancreatic metastasis originating from small cell lung cancer (SCLC). During a multidisciplinary team discussion, we reached a consensus in diagnosing the patient with post-transformation small cell carcinoma alongside moderately severe pancreatitis, which was determined to be a consequence of pancreatic metastasis. The patient received a regimen of etoposide and cisplatin chemotherapy. This unique clinical case highlights the importance of further investigating the factors contributing to pancreatic metastasis in patients with lung cancer, as the underlying mechanisms remain unclear. Understanding these exceptional metastatic events is vital in devising effective therapeutic strategies and improving patient prognosis. Our findings emphasize the need for continued surveillance and comprehensive management of lung cancer patients, particularly those with resistant forms of the disease, to promptly identify and address the progression of metastatic events to uncommon sites such as the pancreas.